Consistency of neuropsychological and driving simulator assessment after neurological impairment. Issue 4 (4th July 2022) - Cizman Staba, Ursa; Klun, Tara; Stojmenova, Kristina; Jakus, Grega; Sodnik, Jaka
Abstract: Deficits in attentional and executive functioning may interfere with driving ability and result in a lower level of fitness to drive. Studies show mixed results in relation to the consistency of neuropsychological and driving simulator assessment. The objective of this study was to investigate the consistency of both types of assessment. Ninety-nine patients with various neurological impairments (72 males; M  = 48.98 years; SD  = 17.27) performed a 30-minute drive in a driving simulation in three different road settings; a (non-)residential rural area, a highway and an urban area. They also underwent neuropsychological assessment of attention and executive function. An exploratory correlational analysis was conducted. We found weak, but significant correlations between attention and executive function measures and more efficient driving in the driving simulator. Distractibility was associated with the most simulator variables in all three simulated road settings. Participants who were better at maintaining attention, eliminating irrelevant information and suppressing inappropriate responses, were less likely to drive above the speed limit, produced a less jerky ride, and used the rearview mirror more regularly. A lack of moderate or strong significant correlations (inconsistency) between traditional neuropsychological and simulator assessment variables may indicate that they don't evaluate the same cognitive processes.